Simulasi dan Pengukuran Unjuk Kerja Sistem Pompa Air-Energi Surya Untuk Kota Banda Aceh - Ahmad Syuhada; Razali Thaib; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2013)
The use of electrical energy to supply either clean water or water for agricultural purpose persistently to increase in line with the population growth. The primary objective of this study is to conduct a feasibility study of the utilization of solar energy for driving pumps in Aceh Province, to perform computer simulations for designing solar energy water pump system, and to measure the performance of the small scale solar energy water pump system. The analysis result shows that the potential of solar energy in Aceh Privince can be used to drive the pump for irrigation and clean water for the needs of the community. The performance measurement result shows that the 50 Wp PV panel is capable of driving the pump with 60 Watts of power for 4-5 hours, on a cloudy day, and 8-10 hours on a sunny day.